ANALYZING THE EFFECT OF TRANSFORMATIONAL LEADERSHIP PERCEPTION ON TEAM LEARNING IN INDUSTRIAL ORGANIZATIONS: THE MEDIATING ROLE OF AFFECTIVE COMMITMENT - YILMAZ , Rabia (SSD Journal, 2021)
In organizations where transformational leadership is at a high level, employees establish an emotional bond with their team and thus with the organization, and almost become familiar with other team members. In this context, employees attempt to learn much more and teach other team members what they have learned in order to increase team success. In this case, team learning reaches higher levels and as a result of this, the effectiveness and efficiency of the team and the organization increase. Accordingly, in this study, it is aimed to examine the mediating role of affective commitment in the effect of transformational leadership on team learning. In the study, the questionnaires were conducted with 161 white-collar employees teamed up in the organization located at the motor vehicles industrial organizations operating in Ankara which are included within the scope of the ISO first and second 500 largest industrial organizations. According to the analysis results, the semi-mediating role of affective commitment was found in the effect of transformational leadership on team learning. It was also found that affective commitment had a semi-mediating role in the effect of idealized influence/charisma, inspirational motivation, and individualized consideration on team learning.